The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/la0302145
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Polyelectrolyte Adsorption Cutoff Induced by a Monovalent Salt

Abstract: This work documents a sharp adsorption cutoff for a cationic polymer (poly(dimethylamino ethyl methacrylate)) adsorbing onto a negative surface (silica) from buffered aqueous solution, as a function of ionic strength. In this system, electrostatic attractions drive adsorption, without contribution from chemical or hydrophobic interactions between the polymer and the surface. In the limit of dense surface charge and sparse polymer charge, a small increase in monovalent salt concentration (less than a factor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
76
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 25 publications
11
76
1
Order By: Relevance
“…Enarsson et al 28 and Saarinen et al 29 also observed this behaviour, when they studied the adsorption of CPAM on cellulose fibers and silica surfaces. A similar trend was established by Hansupalak et al 23 results, who measured the adsorbed amount of DMAEMA on silica, as a function of ionic strength at various pH values. When Rojas 34 et al investigated adsorption of a polymer with a low linear charge density, onto an highly charged mica surface, they noted a monotonic desorption upon the addition of salt.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Enarsson et al 28 and Saarinen et al 29 also observed this behaviour, when they studied the adsorption of CPAM on cellulose fibers and silica surfaces. A similar trend was established by Hansupalak et al 23 results, who measured the adsorbed amount of DMAEMA on silica, as a function of ionic strength at various pH values. When Rojas 34 et al investigated adsorption of a polymer with a low linear charge density, onto an highly charged mica surface, they noted a monotonic desorption upon the addition of salt.…”
Section: Introductionsupporting
confidence: 88%
“…The practical relevance of polyion adsorption has generated substantial theoretical [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and experimental 6,16,[20][21][22][23][24][25][26][27][28][29][30][31][32] efforts. As mentioned above, surface interactions in polyelectrolyte solutions can often be regulated by increasing or decreasing the addition of simple salt.…”
Section: Introductionmentioning
confidence: 99%
“…Enarsson et al 20 and Saarinen et al 21 also observed this behaviour, when they studied the adsorption of CPAM on cellulose fibers and silica surfaces. Qualitatively similar findings were noted by Hansupalak et al, 12 who measured the adsorbed amount of DMAEMA on silica, as a function of ionic strength at various pH values. Guzmán et al, 27 on the other hand, observed a monotonically increasing adsorbed amount, as salt was added.…”
Section: Introductionsupporting
confidence: 88%
“…When ionic strength increases, a sharp adsorption cutoff for a polyelectrolyte like DMAEMA adsorbing on an oppositely charged surface takes place in the absence of other interactions [187]. The cutoff is sharper if the polymer is weakly charged.…”
Section: Adsorption Of Polymers On Silica Surfacementioning
confidence: 99%